2021
DOI: 10.1186/s13063-021-05480-6
|View full text |Cite
|
Sign up to set email alerts
|

Financial Incentives for Preventing Postpartum return to Smoking (FIPPS): study protocol for a three-arm randomised controlled trial

Abstract: Background Financial incentives are an effective way of helping women to stop smoking during pregnancy. Unfortunately, most women who stop smoking at this time return to smoking within 12 months of the infant’s birth. There is no evidence for interventions that are effective at preventing postpartum smoking relapse. Financial incentives provided after the birth may help women to sustain cessation. This randomised controlled trial will assess the effectiveness and cost-effectiveness of financial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Many studies have shown a rapid return to smoking post partum, suggesting the use of continued incentive payments post partum to prevent relapse (subject of an ongoing trial, ISRCTN5521821). 19 The current trial shows a clinically important 45 46 increase in birth weight among participants who adhered to their treatment allocation (0.31 kg (95% confidence interval −0.18 to 0.80 kg); 10% of birthweight), similar to the feasibility trial 37 (0.15 kg (−0.62 to 0.80 kg); 5% of birthweight) and to application of average causal effect analysis to the French trial 43 (0.52 kg; 15% of birthweight). A meta-analysis of these and other relevant data would allow a definitive answer to be reached regarding an important birthweight increase 45 46 among those participants who quit smoking with the offer of financial incentives but would not have quit without that offer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown a rapid return to smoking post partum, suggesting the use of continued incentive payments post partum to prevent relapse (subject of an ongoing trial, ISRCTN5521821). 19 The current trial shows a clinically important 45 46 increase in birth weight among participants who adhered to their treatment allocation (0.31 kg (95% confidence interval −0.18 to 0.80 kg); 10% of birthweight), similar to the feasibility trial 37 (0.15 kg (−0.62 to 0.80 kg); 5% of birthweight) and to application of average causal effect analysis to the French trial 43 (0.52 kg; 15% of birthweight). A meta-analysis of these and other relevant data would allow a definitive answer to be reached regarding an important birthweight increase 45 46 among those participants who quit smoking with the offer of financial incentives but would not have quit without that offer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this progress, women who continue to smoke while pregnant might not engage with cessation services 15. Interventions using financial incentives, piloted in the US,1617 led to service developments in the UK 1819. The acceptability of financial incentives to change behaviour depends on: effectiveness (even a small improvement increases acceptability); the type of incentive (grocery vouchers are more acceptable than cash or vouchers for luxury items); and the target behaviour (weight management is more acceptable than smoking cessation) 20.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, financial incentives for antepartum and postpartum smoking cessation should be introduced especially among at-risk groups. Smoking-cessation programmes aimed at pregnant women are said to be highly cost-effective due to the decrease of in-hospital costs associated with prolonged health care and adverse birth outcomes [ 71 , 72 ]. There is a high priority and a rationale to implement the strategy into practice in all societies and populations.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 75% of quitters return to smoking within 6 months after childbirth. Consequently, their children are exposed to passive smoking and are at higher risk of smoking-related illnesses [ 72 ]. It is worth emphasizing that electronic nicotine delivery systems increase the occurrence of SGA births [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is important because maintaining a smoke-free home will enable children to grow up free from the health hazards associated with exposure to tobacco smoke. Evidence from several current trials addressing some of these issues will help to optimise strategies to support implementation of incentives in daily practice 101112…”
mentioning
confidence: 99%